Nonstandard work arrangements and configurations of firm and societal systems - Stavrou, Eleni T.; Parry, Emma; Anderson, Deirdre A. (Taylor and Francis, 2015)
In this study, we proposed and empirically confirmed that the use of nonstandard working arrangements (NSWAs) varies according to firm system and societal cluster. Utilizing the configurational, institutional and cultural perspectives, we explored antecedents to the use of four NSWAs across firms in six countries, expanding the scope of variables examined in relation to NSWAs and capturing context as a way of broadening the theory base on the subject. We found a tendency toward greater use of NSWAs among firm systems that foster internal socialization and career advancement over time as well as national contexts that promote employment protection and/or Institutional Collectivism. Finally, we found national context to be a significant determinant of firm system, reinforcing the importance of aligning national with organizational-level antecedents to the study of NSWAs.
Keywords: comparative HRM; configurational approach; firm system; societal system; working time arrangements